Effect of Chitosan and Liposome Nanoparticles as Adjuvant Codelivery on the Immunoglobulin G Subclass Distribution in a Mouse Model - Agus Haryono; Korrie Salsabila; Witta Kartika Restu; Sri Budi Harmami; Dodi Safari (Journal of Immunology Research)
Background. We investigate the immunogenic properties of chitosan and liposome nanoparticles as adjuvant codelivery against a commercial pneumococcal conjugate vaccine (PCV) in an animal model. Methods. The chitosan and liposome nanoparticles were prepared by ionic gelation and dry methods, respectively. The PCV immunization was performed intradermally in the presence of adjuvants and booster injections which were given without an adjuvant. The Quil-A® was used as a control adjuvant. The ELISA was performed to measure the antibodies against pneumococcal type 14 polysaccharide (Pn14PS). Results. The level of total antibodies against Pn14PS antigen was no different between the mouse groups with or without adjuvant codelivery. Codelivery of the PCV with chitosan nanoparticles as well as the Quil-A adjuvant elicited IgG1, IgG2a, IgG2b, and IgG3 antibodies. Meanwhile, codelivery of liposome nanoparticles elicited mainly IgG1 antibodies against the Pn14PS. Conclusions. The chitosan and liposome nanoparticles as adjuvant codelivery were successfully synthesized. These nanoparticles have different shapes in particle formation, liposome nanoparticle with their unilamellar shape and chitosan nanoparticles in large shape due to the aggregation of small-size particles. Codelivery of chitosan nanoparticles has more effect on the IgG subclass antibody production than that of liposome nanoparticles in a mouse model.